2002
DOI: 10.1109/10.979353
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution estimation of nerve conduction velocity distribution

Abstract: A conduction velocity distribution (CVD) estimator that incorporates volume conductor modeling of the nerve-evoked response is introduced in this paper. The CVD estimates are obtained from two compound nerve action potentials (CNAP) recorded at the skin surface. A third channel is introduced in order to assess the estimator performance in the experimental case. The relevance of using an accurate signal model is shown by comparing the performance of the proposed estimator with a previous approach based on a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…More recently there have been several additional studies including the work of Gonzalez-Cueto, Papadopoulou and Gu [7][8][9]. The study presented by Tu et.…”
Section: Introductionmentioning
confidence: 94%
“…More recently there have been several additional studies including the work of Gonzalez-Cueto, Papadopoulou and Gu [7][8][9]. The study presented by Tu et.…”
Section: Introductionmentioning
confidence: 94%
“…More recently, there have been several additional studies including the work of Gonzalez-Cueto and Parker [7], Papadopoulou (2 ) (t) to the maximal compound evoked potentials Ψ (1) (t) and Ψ (2) (t). The figure is not drawn to scale and is indicative of stimulation and recording sites at convenient locations along the median nerve.…”
Section: Introductionmentioning
confidence: 99%
“…The technique used by the authors is a deconvolution approach based on volume conductor modeling of the surface EMG interference pattern [2]. It makes use of two correlation functions computed from the surface EMG data recorded at the skin surface with a bipolar configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Two representations of the CVD estimate are shown on both figures in correspondence with columns 3 & 4 of Table 1. It has been shown that the smoothed or lowpass filtered estimate help decrease the variance of the estimation [2]. It can also be appreciated that the estimator error is smaller when the filtered estimate is used.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation